Mechanisms of influence: Alcohol industry submissions to the inquiry into fetal alcohol spectrum disorders. (1st June 2016) - Avery, Michelle Rose; Droste, Nicolas; Giorgi, Caterina; Ferguson, Amy; Martino, Florentine; Coomber, Kerri; Miller, Peter
Abstract: Introduction and Aims: Industry groups with vested interests in policy regularly work to protect their profits via the endorsement of ineffective voluntary regulation and interventions, extensive lobbying activity and minimising the health impact of consumption behaviours. This study aims to examine all alcohol industry submissions to the Australian House of Representatives Standing Committee on Social Policy and Legal Affairs into Fetal Alcohol Spectrum Disorders (FASD), to assist in understanding how those with vested interests contribute to policy development. The analysis aims to document the strategies and arguments used by alcohol industry bodies in their submissions and to compare these with known strategies of vested‐interest groups. Design and Methods: All 92 submissions to the Inquiry were screened to include only those submitted by alcohol industry bodies (five submissions). Content domains were derived based on the major themes emerging from the industry submissions and on common vested‐interest behaviours identified in previous literature. Results: The following content categories were identified: Concerns about FASD; Current industry activities and FASD prevention; Value of mandatory warning labels; and Credibility of independent public health researchers and organisations. Discussion and Conclusions: Alcohol industry submissions sought to undermine community concern, debate the evidence, promote ineffective measure which are no threat to the profit margins and attack independent health professionals and researchers. In doing so, their behaviour is entirely consistent with their responses to other issues, such as violence and chronic health, and copies the tactics employed by the tobacco industry. [Avery MR, Droste N, Giorgi C, Ferguson A, Martino F, Coomber K, Miller P. Mechanisms of influence: Alcohol industry submissions to the inquiry into fetal alcohol spectrum disorders. Drug Alcohol Rev 2016;35:665‐672]